Harry Potter and the sorcerer's stone [videorecording] ([Burbank, CA] : Warner Brothers, 2002)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School for Wizards and Witches.